IMPLEMENTASI GAYA KEPEMIMPINAN KEWIRAUSAHAAN PENGURUS KOPERASI DALAM MENINGKATKAN USAHA ANGGOTA KOPERASI KELOMPOK TANI - Asriati, Nuraini; Wardani, Sandra Fitria (Universitas Tanjungpura, 2023)
Entrepreneurial leadership is the leadership style of an entrepreneur who can seek to inspire members to work with the direction of a board towards its members in an effort that can be achieved together. The better the leadership style of the management results in good organizational performance. This study aims to analyze the leadership style in the Tunas Harapan Farmer Group Cooperative, Tebas District. The research approach used is qualitative research. The method used uses the methods of interviewing, observation and documentation. Instrumen penelitian yang digunakan adalah lembar wawancara, lembar observasi dan dokumenter. The participants involved in this study were the board of the tunas harapan cooperative consisting of the chairman, deputy, secretary, and treasurer as well as 3 members of the cooperative. Analysis of data used in thematic research analysis. The results showed that the entrepreneurial leadership of cooperative administrators was dominant in the democratic leadership style by 75%, authoritarian by 5% and laiisse Fraize by 20%. The recommendation of this study is that cooperative administrators should better carry out the entrepreneurial leadership style in a combination of styles so that it is attached to a philosophy, behavior, personality and skills of its members in improving their business performance so that they are more effective and efficient. The recommendation of this study is that cooperative administrators should better carry out the entrepreneurial leadership style in a combination of styles so that it is attached to a philosophy, behavior, personality and skills of its members in improving their business performance so that they are more effective and efficient